The Philippine defence-development-disaster security paradigm - Avila, Ava; Matthews, Ron (Taylor & Francis, 2022)
The Philippines suffers from three threats to its national security. Firstly, unlike advanced states, it faces both external and internal assaults on its political and territorial sovereignty. Secondly, self-sustaining economic security remains elusive, with the country failing to emulate the economic successes of its ASEAN neighbours, Singapore and Malaysia. Thirdly, the archipelago must constantly contend with the destabilising effects of natural disasters, including volcanic eruptions, typhoons, and earthquakes. Manila's policy responses to these three disparate, but interlinked threats, have been conditioned by four centuries of Spanish, American, and Japanese occupation. The Philippine government remains a work in progress as diverse efforts to build institutional capacity have produced uneven results. Nevertheless, recent innovative policy approaches are instructive. These are framed around what might be termed a D3 (Defence-Development-Disaster) security paradigm, covering external military security, internal security and non-traditional security, including the Duterte administration's “drug war”, as an element of national security alongside counter-insurgency and counter-terrorism.
Keywords: Philippines; defence; development; disaster; security